The railway track and its long term behaviour : a handbook for a railway track of high quality - Tzanakakis, Konstantinos (Springer Tracts on Transportation and Traffic, 2013)
A proper quality of a track and other infrastructure objects represents a basic requirement for train safety and punctuality. Most of the physical systems and their components deteriorate over time. This affects performance and may lead to failures. Albert Einstein said, "You have to learn the rules of the game. And then you have to play better than anyone else." Only if we understand how the whole system works, taking into account its imperfections and how they influence its quality and performance will we be able to learn the rules of the game and "play better." The book provides the readers with the necessary functional knowledge of track behaviour and comprehensively covers the function of the various track components, their interaction as elements of the track system, as well as the interaction of the track with railway vehicles. By presenting important tools for a deep understanding of track-behaviour this book aims to be a reference guide for infrastructure managers and to help them to find ways improving track quality for optimum long-term behaviour.